The relationship between external debt and economic growth in Morocco: Empirical investigation - Zouirchi, Houda (2023)
The relationship between the external public debt and the economic growth of countries has always been controversial. The purpose of this article is to analyze empirically the impact of the external public debt and the economic growth of Morocco in the period 1984 to 2021. In order to achieve that, a methodology based on a proposal of an empirical and theoretical literature review that treats this problem has been used on the first hand. On the other hand, an econometric analysis has been utilized to detect if there is a long-term growing relationship between the external debt and the Moroccan economic growth.